Enhanced performance of the microalga Chlorella sorokiniana remotely induced by the plant growth-promoting bacteria Azospirillum brasilense and Bacillus pumilus - Amavizca, Edgar; Bashan, Yoav; Ryu, Choong-Min; Farag, Mohamed A.; Bebout, Brad M.; de-Bashan, Luz E. (Scientific reports, 2017)
Remote effects (occurring without physical contact) of two plant growth-promoting bacteria (PGPB) Azospirillum brasilense Cd and Bacilus pumilus ES4 on growth of the green microalga Chlorella sorokiniana UTEX 2714 were studied. The two PGPB remotely enhanced the growth of the microalga, up to six-fold, and its cell volume by about three-fold. In addition to phenotypic changes, both bacteria remotely induced increases in the amounts of total lipids, total carbohydrates, and chlorophyll a in the cells of the microalga, indicating an alteration of the microalga’s physiology. The two bacteria produced large amounts of volatile compounds, including CO 2 , and the known plant growth-promoting volatile 2,3-butanediol and acetoin. Several other volatiles having biological functions in other organisms, as well as numerous volatile compounds with undefined biological roles, were detected. Together, these bacteria-derived volatiles can positively affect growth and metabolic parameters in green microalgae without physical attachment of the bacteria to the microalgae. This is a new paradigm on how PGPB promote growth of microalgae which may serve to improve performance of Chlorella spp. for biotechnological applications.